Probing microdomain Ca2+ activity and synaptic transmission with a node-based tripartite synapse model - Liu, Langzhou; Gao, Huayi; Li, Jinyu; Chen, Shangbin (Frontiers in Network Physiology, 2023)
Astrocytic fine processes are the most minor structures of astrocytes but host much of the Ca2+ activity. These localized Ca2+ signals spatially restricted to microdomains are crucial for information processing and synaptic transmission. However, the mechanistic link between astrocytic nanoscale processes and microdomain Ca2+ activity remains hazily understood because of the technical difficulties in accessing this structurally unresolved region. In this study, we used computational models to disentangle the intricate relations of morphology and local Ca2+ dynamics involved in astrocytic fine processes. We aimed to answer: 1) how nano-morphology affects local Ca2+ activity and synaptic transmission, 2) and how fine processes affect Ca2+ activity of large process they connect. To address these issues, we undertook the following two computational modeling: 1) we integrated the in vivo astrocyte morphological data from a recent study performed with super-resolution microscopy that discriminates sub-compartments of various shapes, referred to as nodes and shafts to a classic IP3R-mediated calcium signaling framework describing the intracellular Ca2+ dynamics, 2) we proposed a node-based tripartite synapse model linking with astrocytic morphology to predict the effect of structural deficits of astrocytes on synaptic transmission. Extensive simulations provided us with several biological insights: 1) the width of nodes and shafts could strongly influence the spatiotemporal variability of Ca2+ signals properties but what indeed determined the Ca2+ activity was the width ratio between nodes and shafts, 2) the connectivity of nodes to larger processes markedly shaped the Ca2+ signal of the parent process rather than nodes morphology itself, 3) the morphological changes of astrocytic part might potentially induce the abnormality of synaptic transmission by affecting the level of glutamate at tripartite synapses. Taken together, this comprehensive model which integrated theoretical computation and in vivo morphological data highlights the role of the nanomorphology of astrocytes in signal transmission and its possible mechanisms related to pathological conditions.